2022
DOI: 10.1088/1748-605x/ac6eab
|View full text |Cite
|
Sign up to set email alerts
|

The construction of a self-assembled coating with chitosan-grafted reduced graphene oxide on porous calcium polyphosphate scaffolds for bone tissue engineering

Abstract: Bone regeneration in large bone defects remains one of the major challenges in orthopedic surgery. Calcium polyphosphate (CPP) scaffolds possess excellent biocompatibility and exhibits good bone ingrowth. However, the present CPP scaffolds lack enough osteoinductive activity to facilitate bone regeneration at bone defects that exceed the critical size threshold. To endow CPP scaffolds with improved osteoinductive activity for better bone regeneration, in this study, a self-assembled coating with chitosan-graft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 66 publications
(77 reference statements)
0
4
0
Order By: Relevance
“…The quantitative analysis result of ARS extracts (Figure e) indicated that the SCPP/MoS 2 -MET group had a stronger mineralization capacity compared with the other groups. This suggested SCPP/MoS 2 -MET possessed a better osteogenic potential under inflammatory conditions, both early (demonstrated by ALP staining) and late (demonstrated by ARS staining) stage . This could be attributed to the long-term release of metformin acting as an anti-inflammatory agent.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…The quantitative analysis result of ARS extracts (Figure e) indicated that the SCPP/MoS 2 -MET group had a stronger mineralization capacity compared with the other groups. This suggested SCPP/MoS 2 -MET possessed a better osteogenic potential under inflammatory conditions, both early (demonstrated by ALP staining) and late (demonstrated by ARS staining) stage . This could be attributed to the long-term release of metformin acting as an anti-inflammatory agent.…”
Section: Resultsmentioning
confidence: 90%
“…This suggested SCPP/MoS 2 -MET possessed a better osteogenic potential under inflammatory conditions, both early (demonstrated by ALP staining) and late (demonstrated by ARS staining) stage. 51 This could be attributed to the long-term release of metformin acting as an anti-inflammatory agent. Digital photos of ALP staining and ARS staining were displayed in Figure S9.…”
Section: Antibacterial Activity Of Scaffold-samples Inmentioning
confidence: 99%
“…They were deconvoluted into three principal peaks near 288.2, 286.6 and 284.8 eV, which were assigned O-C=O, C-O/C-N, and C-C bonds, respectively[ 35 , 36 ]. Figure 4D showed that the N 1s spectra and the peaks near 399.8 eV were attributed to amidogen groups (-NH 3+ )[ 37 ]. CHA-0 and CHA-H were selected because they were most likely to differ, and in fact all samples had similar C 1s and N 1s spectra.…”
Section: Resultsmentioning
confidence: 99%
“…Many applications are proposed for these carbon-based nanomaterials addressing different biomedical issues [6][7][8][9][10]. In recent years, many research groups have reported antibacterial performance for graphene, graphene oxide (GO), reduced GO, and other functionalized two and threedimensional nanomaterials based on the graphene family [11][12][13][14]. As a two-dimensional (2D) nanomaterial, GO possesses the significant properties of graphene such as a large specific surface area, and has a variety of oxygen-containing functional groups, making it a good candidate for an antibacterial material due to effective GO/bacteria interaction at the atomic scale.…”
Section: Introductionmentioning
confidence: 99%